Analisis Pengaruh Incremental Discount Pada Model Persediaan Multi Item Dengan Faktor Kedaluwarsa dan Kendala Kapasitas - Silitonga, Roland; Kristiana, Leo Rama; Abel, Philo (Universitas Katolik Parahyangan, 2024)
The retail industry engaged in the pharmaceutical sector such as pharmacies sells various types of medicinal products and medical chemicals with fluctuating demand characteristics. This is due to the emergence of diseases that cannot be predicted with certainty. Inventory management is an important aspect to ensure the availability of medicines when needed while still being able to minimize losses both from retained capital on goods and potential expiration. Medicinal products themselves have a certain shelf-life, so products that have expired cannot be used again and cause losses to company. The form of inventory management policy is the order lot size, time between orders and reorder points. To determine the size of the order lot, in addition to the expiration aspect, the limitations of the warehouse as a place of storage and purchase discount factors need to be considered. The existence of a discount policy from suppliers can be used to minimize purchasing costs which are a component of inventory costs. The form of the discount policy that is generally given is the all-unit discount, but for certain types of products the policy given is an incremental discount. The purpose of this study is to build a multi-item probabilistic inventory model by considering the expiration factor, warehouse capacity constraints, and purchasing discount policies. This research will compare two discount policies, namely incremental discount and all unit discount. Based on the results of the sensitivity analysis, it is known that the model is sensitive to the parameters of unit discount provisions, good goods fraction, and holding costs.